PENGARUH E-WALLET DAN GAYA KONSUMTIF TERHADAP BELANJA ONLINE - Swastika, Yuan (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study is entitled The Effect of E-Wallet and Consumptive Style on Online Shopping. The aim is to find out the Effect of E-Wallet and Consumptive Style on Online Shopping, the Effect of E-Wallet on Online Shopping, and the Effect of Consumptive Style on Online Shopping. In recent years, technology has come a long way and has changed the way people do things, including shopping. Online shopping has become a growing trend and many people are starting to shop online. The use of e-wallets and consumptive styles have also increased and have contributed to the increase in online shopping. Therefore, this study aims to determine the effect of e-wallets and consumer styles on online shopping. This study used a survey method with a purposive sampling technique. The number of samples used is 81 people who use e-wallets and shop online. The results of this study indicate that e-wallets do not have a significant effect on online shopping, while consumptive style has a significant effect on online shopping.